Net technique for intraocular lens support in aphakia without capsular support - De Novelli, Fernando José (Int J Retina Vitreous, 2017)
BACKGROUND: This paper describes a modified surgical technique for intraocular lens implantation in aphakic eyes with no capsular support. METHODS: Retrospective case series. Seventeen eyes of 17 aphakic patients with no capsule support underwent intraocular lens (IOL) implantation using a standardized technique in which a net was created at the ciliary sulcus plane with two threads forming a net pattern. The net was used as support for the IOL. Follow-up ranged from 6 to 38 months, with an average of 23 months. RESULTS: In all cases, the IOL was safely implanted and remained stable during the follow-up. In 16 eyes, the IOL remained well centered; in one eye, slight decentration was observed. Distance-corrected visual acuity improved by a mean of 4 lines, from 1.13 (LogMAR) to 0.52 (P = 0.01). CONCLUSION: This technique might be especially useful in cases of insufficient capsular support associated with tissue loss or iris atrophy. In these cases, iris fixation is not feasible; thus, the only surgical alternative is IOL scleral fixation. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s40942-017-0085-8) contains supplementary material, which is available to authorized users.